O PRONATEC e a política de formação da classe trabalhadora no contexto da proclamada sociedade do conhecimento: um exame onto-crítico - Lemos, Ana Thyara Leal (2016)
The aim of this dissertation was to analyze, under the light of the Marxist, the training policy for work postulated by the National Technical Education and Access to Employment (Portuguese acronym Pronatec) under the speech of a proclaimed society of knowledge, trying to understand the expressivity of this speech and the ideological determinations that aligns with training policies to the employability in the mentioned program. Analyzed that in a crisis context the structure of the capitalist system, that became severe intensification social barbarism and destruction as a logic of systemic reproduction, attacking inexorably all the complex social praxis, impose itself an educational project in which embody a speech of employability and the need in technical qualification of working class. Inside of this logic, was created the National Technical Education and Access to Employment (Portuguese acronym Pronatec), sanctioned by the Law 12.513/2011 as expansion policy professional education, has the objective to foment a training for work and evincing strengthening the relationship between the education and the market demands. Based onthe speech of a proclaimed society of knowledge, the program consolidates a hurried qualification of working class, professional education still listed as essential component of solving the social problems and as essential element for the economic progress of the country. To handle this problem, this research bibliographic theoretical and documental essentially based in studies of: Marx (1996; 2010); Lessa (2012); Mészáros (1996; 2011); Freres (2008; 2013); Barbosa (2008); Santos (2005; 2009); Lima (2011), besides we have the law that ratify the program and documents obtained from Ministry of Education (Portuguese acronym MEC), from Secretariat of Vocational and Technological Education, and the reports produced by Brazilian Federal Court of Auditors and by the General Comptroller’s Office, and others. In this investigative bias, the research indicate that Pronatec has proved an expressive strategy of capital in crisis, fulfill two essential functions to its reproduction: first it refers to private sector financing through the state; second, of ideological, disqualifies the working class in fragmented courses to this become formed on precise sense of the market logic.